2000
DOI: 10.1016/s0016-7037(99)00437-8
|View full text |Cite
|
Sign up to set email alerts
|

Seawater pH control on the boron isotopic composition of calcite: evidence from inorganic calcite precipitation experiments

Abstract: Abstract-Experiments involving boron co-precipitation with calcite have been carried out inorganically under controlled pH conditions (7.9 Ϯ 0.05, 8.3 Ϯ 0.05 and 8.6 Ϯ 0.05) to determine the dependence of the boron isotopic composition (␦ 11 B) of calcite on the pH of seawater. Another purpose of these experiments was to estimate the magnitude of the biogenic influence on the ␦ 11 B value of foraminifera by comparing their boron isotopic composition with that of the inorganic calcite over a common pH range. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
179
6
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(201 citation statements)
references
References 21 publications
15
179
6
1
Order By: Relevance
“…381 Although pH measurements have never been con-382 ducted on this species, it is well known that the 383 addition of respiratory CO 2 decreases pH in sym-384 biont-bearing foraminifera by up to 0.3 units 385 (JÖrgensen et al, 1985;Rink et al, 1998;Wolf-386 and is therefore expected to 387 in£uence G. bulloides similarly. Comparison of 388 this datum point with data from inorganic precip-389 itation experiments (Sanyal et al, 2000) demon-390 strates that G. bulloides falls slightly below the 391 inorganic precipitation curve (Fig. 2).…”
Section: B Ho «Nisch Et Al / Marine Micropaleontology 928 (2003) 1^10mentioning
confidence: 86%
See 1 more Smart Citation
“…381 Although pH measurements have never been con-382 ducted on this species, it is well known that the 383 addition of respiratory CO 2 decreases pH in sym-384 biont-bearing foraminifera by up to 0.3 units 385 (JÖrgensen et al, 1985;Rink et al, 1998;Wolf-386 and is therefore expected to 387 in£uence G. bulloides similarly. Comparison of 388 this datum point with data from inorganic precip-389 itation experiments (Sanyal et al, 2000) demon-390 strates that G. bulloides falls slightly below the 391 inorganic precipitation curve (Fig. 2).…”
Section: B Ho «Nisch Et Al / Marine Micropaleontology 928 (2003) 1^10mentioning
confidence: 86%
“…Comparison of the boron isotopic composition of the 2 symbiont-bearing foraminifera Orbulina universa and the 3 symbiont-barren Globigerina bulloides (¢lled circles) taken 4 from plankton tows and inorganic carbonates (open circles 5 and solid line; Sanyal et al, 2000). As the inorganic carbon-6 ate was also precipitated in arti¢cial seawater, the N 11 B val-7 ues of Sanyal et al (2000) were converted to the natural sea-8 water scale according to Zeebe and Wolf-Gladrow (2001, The N 11 B of symbiont-barren Globigerina bul-373 loides (19.0 þ 0.9x) was 1.4x lower than that 374 of the Orbulina universa shells collected from the 375 same plankton tows. Because this is the ¢rst N 11 B 376 datum ever measured on a symbiont-barren spe-377 cies, it cannot be compared to literature data.…”
Section: B Ho «Nisch Et Al / Marine Micropaleontology 928 (2003) 1^10mentioning
confidence: 99%
“…Many studies have indicated that only B(OH) − 4 is incorporated preferentially into corals marine carbonates (Vengosh et al, 1991;Hemming and Hanson, 1992;Hemming et al, 1995;Spivack et al, 1993;Sanyal et al, 1996Sanyal et al, , 2000. Under this circumstance, all the δ 11 B values of carbonates are considered to be paralleled with the theoretical δ 11 B sw3 and are lower than that of the parent seawater; α carb−sw between carbonates and seawater are lower than 1 and increase with pH.…”
Section: Model 3: Both Chemical Reaction and Adsorption Of Boron Incomentioning
confidence: 98%
“…The incorporation of Mg into coral skeleton is controlled by varying factors. Mg can exist in the form of brucite in corals (Smith and Delong, 1978;Nothdurft et al, 2005) and Mg content in scleractinian corals varies between different genera and localities (Fallon et al, 1999). Nothdurft et al (2005) studied brucite in living scleractinian corals colonies (Acropora, Pocillopora, Porites) from subtidal and intertidal settings in the Great Barrier Reef, Australia, and subtidal Montastraea from the Florida Keys, United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation